Antiphospholipid Antibodies Are Not Associated with Clinical Parameters or Prognostic Outcomes in Patients with Non-Hodgkin's Lymphoma - Pal, Rimesh; Varma, Subhash; Ahluwalia, Jasmina; Prakash, Gaurav (Hämostaseologie, 2020)
Background Antiphospholipid antibodies (APAs) are found quite frequently in patients with non-Hodgkin’s lymphoma (NHL). However, the clinical significance of these antibodies is largely unknown. This study aims to delineate the clinical and prognostic role of APAs in NHL patients.Patients and Methods  Consecutive patients of NHL were screened for lupus anticoagulant (LA), IgG/IgM anticardiolipin antibody, and IgG/IgM anti-β2-glycoprotein I at the time of diagnosis. Baseline investigations, staging, and treatment were done as per institutional protocol. Patients were followed up until the last known outpatient visit or death. All were screened at each visit for any thromboembolic event. The association of APA status with baseline NHL characteristics and treatment response was evaluated by univariate analysis. Kaplan–Meier survival analysis was used to compare the final outcome in patients with or without APAs. Patients who were initially APA positive were retested for the corresponding antibody at the end of chemotherapy.Results Twenty-four out of 105 patients (22.8%) were APA positive at diagnosis. The presence of APA was not significantly associated with NHL stage, histology, International Prognostic Index score, activated partial thromboplastin time, or treatment response. The median duration of follow-up was 15 months. Only four patients developed venous thrombosis; none was APA positive. There was no statistically significant difference in overall survival between the two groups (p = 0.471). Patients, who were APA positive initially, tested negative at the end of treatment, irrespective of treatment response.Conclusion APAs are encountered more frequently in NHL patients than in the general population. However, APAs do not correlate with disease severity, thrombosis risk, treatment outcome, or overall survival.
Keywords: non-Hodgkin's lymphoma; antiphospholipid antibodies; lupus anticoagulant; anticardiolipin antibody; anti-β2-glycoprotein I